Unifying Scheme for the Biosynthesis of Acyl‐Branched Sugars: Extended Substrate Scope of Thiamine‐Dependent Enzymes. (28th January 2022) - Steitz, Jan‐Patrick; Krug, Leonhard; Walter, Lydia; Hernández, Karel; Röhr, Caroline; Clapés, Pere; Müller, Michael
Abstract: Thiamine diphosphate (ThDP) dependent enzymes are useful catalysts for asymmetric C−C bond formation through benzoin‐type condensation reactions that result in α‐hydroxy ketones. A wide range of aldehydes and ketones can be used as acceptor substrates; however, the donor substrate range is mostly limited to achiral α‐keto acids and simple aldehydes. By using a unifying retro‐biosynthetic approach towards acyl‐branched sugars, we identified a subclass of (myco)bacterial ThDP‐dependent enzymes with a greatly extended donor substrate range, namely functionalized chiral α‐keto acids with a chain length from C4 to C8 . Highly enantioenriched acyloin products were obtained in good to high yields and several reactions were performed on a preparative scale. The newly introduced functionalized α‐keto acids, accessible by known aldolase‐catalyzed transformations, substantially broaden the donor substrate range of ThDP‐dependent enzymes, thus enabling a more general use of these already valuable catalysts. Abstract : The lipopolysaccharides (LPSs) of bacteria have branched sugars in their outer cell membrane with long, highly modified side chains. LPSs are often crucial factors in the pathogenesis of the bacteria. A unifying explanation of the biosynthesis of these highly interesting structures is introduced, based on the investigation of ThDP‐dependent enzymes responsible for the linkage of the side chain and the sugar core.